On NCT- Set Theory - Dheargham Ali Abdulsada; L. A. A. Al-Swidi; Mustafa H. Hadi (Neutrosophic Sets and Systems, 2024)
We introduce a new class of neutrosophic crisp set, and then it presented some operations via this sets like,